PERANCANGAN SISTEM PEMBAYARAN MAKANAN DAN MINUMAN BERBASIS WEB PADA CAFE RUMAH SI DALANG MENGGUNAKAN METODE R&D - Dwi Rizky Ramadhani; Muhammad Iqbal; Abdul Khaliq (CV. Hawari, 2026)
The rapid advancement of information technology has significantly influenced various sectors, including payment methods in the culinary business. Manual payment processes often result in delays, inaccuracies in recording, and lack of transparency. This study aims to design and implement a webbased payment system for Cafe Rumah Si Dalang using the Research and Development (R&D) approach. The research process includes requirement analysis, system design, implementation, and testing. The findings indicate that the developed system can streamline the payment process, enhance accuracy, and minimize human errors. Its user-friendly interface allows both cashiers and customers to use the system efficiently. This research is expected to serve as a digital payment solution for culinary businesses and provide a reference for future development, including QRIS integration and automated financial reporting features.